Sebuah analisis Pengaruh Inflasi, Suku Bunga dan Nilai Tukar Terhadap Perkembangan Pariwisata di Indonesia - bagas budi wicaksono (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2022)
This research was conducted with the aim of knowing the effect of inflation, interest rates and exchange rates on the development of tourism in Indonesia. Researchers used a quantitative approach through secondary data that was processed in multiple linear regression models. The results of the study indicate that equations (1) and (2) have the result that all variables have a less significant effect (p-value > 0.05) where inflation and exchange rates have a negative effect and interest rates have a positive effect on sector development. tourist. This indicates that the greater inflation or price increases and the strengthening of the rupiah exchange rate per 1 USD, the number of foreign tourists and the length of stay of tourists will decrease. Meanwhile, interest rates have a positive influence on the development of the tourism sector. The appropriate policy recommendations are: (1) The government must be able to maintain monetary economic stability, (2) optimize the performance of tourism SOEs to increase the number of arrivals and length of stay of foreign tourists, and (3) provide cheap tour packages for neighboring countries.